Factors associated with the institutionalization of a physical activity program in Australian elementary schools. Issue 6 (26th July 2019) - Bourke, Matthew; Hilland, Toni A; Craike, Melinda
Abstract: The health benefits of classroom-based physical activity programs may only be sustained if programs are continually implemented over time. Despite the importance of instituting physical activity programs to ensure their continued implementation, little is known about factors associated with institutionalization of programs at a school level. The purpose of this study is to examine how school context, principal characteristics, and program attributes are associated with the institutionalization of Bluearth Foundation's Active Schools program in Australian elementary schools. Current principals from schools who participated in the Active Schools program between 2015 and 2017 reported the level of institutionalization of the program, school context, principal characteristics, and perceived attributes of the program. Univariate associations were calculated using Pearson's correlation coefficient, independent sample t -tests and one-way ANOVA. Linear regression using backward deletion was used to calculate significant or marginally significant ( p < .1) multivariate associations. Thirty of the 211 eligible principals participated in the study. School capacity ( r = .617, p < .001); perceived student behavioral ( r = .577, p < .001), health ( r = .499, p < .001), and enjoyment benefits ( r = .529, p < .001), relative advantage ( r = .417, p = .022), observability ( r = .385, p = .036), and having the program delivered by a Bluearth coach at the time of the study (η  2 = .426, p < .001) all had a significant positive univariate association with institutionalization. School capacity (β = 1.802, p = .001), observability (β = 0.902, p = .061), and having the program delivered by a Bluearth coach at the time of the study (β = 2.580, p = .003) remained significant in the final multivariate model. Results suggest that schools that have someone who can provide support implementing a program are more likely to institute the program into policies and practices. It is also important that school administrators have the tools to evaluate the benefits of physical activity programs and to perceive them as being beneficial for their students. However, schools may struggle to institutionalize physical activity programs after formal program delivery has concluded.